Sandboxes: Testing the strategy in Malawi - Carter, Alice (EdTech Hub, 2020)
Written by Alice Carter This is the second in this series about our sandboxes. If you haven’t already, read about our approach to experimentation. Across the Hub, we’re proponents of using our tools and approaches on our own thinking. For innovation, that meant testing the assumptions we were making about how and if the sandboxes …
Library Catalog: edtechhub.org Section: general KerkoCite.ItemAlsoKnownAs: 2405685:785EE55K
Keywords: C:Malawi; F:Sandbox; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Sandboxes: My experience participating in the sandbox alpha - Kumasewera, Pilirani (EdTech Hub, 2020)
This is the third in this series about our sandboxes. If you haven’t already, read about our approach to experimentation and how we tested our sandbox strategy out in Malawi.
Library Catalog: edtechhub.org Section: general KerkoCite.ItemAlsoKnownAs: 2405685:CE3XH7JY
Keywords: F:Sandbox; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Statement by Minister of Education, Hon. Agnes Nyalonje, on Re-Opening of Schools, Colleges, Universities and International Schools on 27 August, 2020 in Lilongwe | United Nations in Malawi - Malawi Minister of Education (2020)
I have called for this press briefing to announce to the nation that Schools, Colleges, Universities and International Schools will re-open on 7th Sept 2020
KerkoCite.ItemAlsoKnownAs: 2339240:N4W98RSH 2405685:2YPQERK7

Will COVID-19 help to clarify ICT integration into education in Malawi? - Gondwe, Foster (The Education and Development Forum (UKFIET), 2020)
This blog was written by Foster Gondwe, Lecturer at the School of Education, University of Malawi, and currently a PhD student at Hiroshima University, Japan. Preamble To join global efforts in curbing the spread of COVID-19, the Ministry of Education, Science and Technology (MoEST) in Malawi closed all schools, colleges and universities from Monday, 23rd […]
KerkoCite.ItemAlsoKnownAs: 2339240:J8AT3YEK 2405685:JKDJKT9J

High Court stops Malawi's 21-day coronavirus lockdown - Montsho, Molaole (2020)
The Lilongwe High Court in Malawi has granted Human Rights Defenders Coalition (HDRC) an order blocking the government from effecting a 21-day lockdown meant to curb the spread of Covid-19.
KerkoCite.ItemAlsoKnownAs: 2405685:IKJMHAAW

Tablet-based Learning for Foundational Literacy and Math: An 8-month RCT in Malawi - Levesque, Karen; Bardack, Sarah; Chigeda, Antonie (2020)
Our 8-month randomized controlled trial (RCT) in government primary schools in Malawi shows significant positive effects for learners in overall literacy and in key early math skills, with similarly positive results for both girls and boys.
KerkoCite.ItemAlsoKnownAs: 2339240:2MD5BSLB 2405685:2MMJYNCA

National education sector investment plan 2020-2030 - Malawi Ministry of Education (Government of Malawi, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:6CF6ZTGI 2405685:UTJ8A7W5

National Household Survey on Access and Usage of ICT Services in Malawi 2019 - National Statistical Office (2020)
KerkoCite.ItemAlsoKnownAs: 2405685:8XN2BTBI

National COVID-19 Preparedness and Response Plan - Republic of Malawi (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:9ISTURV3 2405685:46BPCHFP

The Social Cash Transfer Programme (SCTP) - Government of Malawi; UNICEF (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:4N4VCSLX 2405685:FU7VWMA2

Malawi Vision 2063 Document - National Planning Commission (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:M39XQECB 2405685:IYB8C7VR

Malawi – Fifth Integrated Household Survey 2019-2020 - National Statistical Office (World Bank Microdata Library, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:WQNKCSRI 2405685:KWDWZ5RP

Malawi ICT and Digitalization Policy Roadmap 2022-2026 (Draft) - The Presidential Delivery Unit Digitalization Labs (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:M7X7ND37 2405685:VAIVNKWI

Proposal for GPE Accelerated Funding for COVID-19 Response (Malawi) - Global Partnership for Education (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:FJXR8BZE 2405685:64GPW6ZN

Proposal for GPE Accelerated Funding for COVID-19 Response: Malawi - GPE (Global Partnership for Education, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:2ZSCUCA8 2405685:JW8RHUVL

Top 10 lessons learned from implementing remote learning through IVR in Malawi - Carrol, Dr. Bidemi (RTI International, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:L6GFWQZH 2405685:AJJ6R8BU

Teachers and mothers join forces to keep girls in school in Malawi - United Nations Population Fund (Africa Renewal, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:MKIFTFHW 2405685:ACCDGUZ7

Private education and compliance with the Abidjan Principles: A study of Malawi, Mozambique, Tanzania and Nigeria - Unterhalter, Elaine; Robinson, Lynsey; Luis, Jose; Canelhas, Benito; Coysh, Joanne (ActionAid, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:DTPLLZ6M 2405685:9NNITJSL

World librarians: A socio-technical system providing library search services to offline schools and libraries in Malawi - Schweik, Charles M.; Meyer, Carl; Chinkondenji, Pempho; Smith, Jeremy; Mchenga, Promise (World Development Perspectives, 2020)
Publisher: Elsevier shortDOI: 10/ghgn56 KerkoCite.ItemAlsoKnownAs: 10/ghgn56 2405685:C2FTH5HS

A district level study on the deployment, allocation and utilisation of teachers between and within Malawi's primary schools: an accountability and political settlements approach - Zubairi, Asma (REAL Centre, Faculty of Education, University of Cambridge, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:A5LNBAQR 2405685:Y4HQUGBA

Building effective COVID-19 Education Response Plans: Insights from Africa and Asia - Kimenyi, Eric; Otieno, Jennifer; Kaye, Tom (EdTech Hub, 2020)
previousshortDOI: 10/ghgk6r previousDOI: 10.5281/zenodo.3884302 EdTechHub.Source: 2405685:6W2UWE89 EdTechHub.Source: <this> shortDOI: 10/ghgk6r KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3884302 10.53832/edtechhub.0041 10/ghgk6r 2129771:2MD2QL8K 2339240:7QEJ68RG 2405685:6W2UWE89 2405685:7HQN2HAD
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Back-to-School Campaigns Following Disruptions to Education - Chuang, Rachel; Kaye, Tom; Moss Coflan, Caitlin; Haßler, Björn (EdTech Hub, 2020)
This EdTech Hub Helpdesk response focuses on back-to-school campaigns following disruptions to education, ensuring that children rapidly return to school as soon as it is safe and practical. Key themes of effective school re-openings are examined in the context of modalities used to deliver distance learning (e.g., radio, television).
ZenodoArchiveID: 3878423 previousshortDOI: 10/ghgk6n previousshortDOI: 10/ghgk6n previousDOI: 10.5281/zenodo.3878423 previousshortDOI: 10/ghgk6n EdTechHub.Source: 2405685:DS66UGW4 EdTechHub.Source: <this> shortDOI: 10/ghgk6n KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3878423 10.53832/edtechhub.0019 10/ghgk6n 2129771:GKIQY5RP 2339240:29BIZJM5 2339240:WSA5X76N 2405685:4Z5W36SI 2405685:DS66UGW4 2405685:IS587WTH
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Sandboxes: our approach to systemic experimentation - Simpson, Lea (EdTech Hub, 2020)
What’s a sandbox you ask? First in the series, this blog explains what you need to know about the Hub’s approach to experimentation and innovation.
Library Catalog: edtechhub.org Section: general KerkoCite.ItemAlsoKnownAs: 2339240:N8IVIWTD 2339240:UM8QDJVD 2405685:EU5H44PP 2405685:T22QNFKK 2405685:XZLUI8BE
Keywords: F:Sandbox; LP: English; _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _zenodoETH

18 large-scale EdTech initiatives on our radar in 2020 - Moss, Caitlin (EdTech Hub, 2020)
During the EdTech Hub’s inception phase so far, one question we hear a lot is: “What interesting or notable EdTech initiatives are you seeing?” Another question usually follows: “Which ones are reaching scale?” This week we have joined the global education community in London for the Education World Forum and BETT meetings. This is a […]
Library Catalog: edtechhub.org Section: general KerkoCite.ItemAlsoKnownAs: 2339240:35E4A2TD 2339240:4LGNB3A8 2339240:AA5FSXJC 2339240:RYJUP2SP 2405685:ATRDA7GD 2405685:BYEPNBQB 2405685:CLFVRHB5 2405685:EIZKB3Q4 2405685:QCXEVZTI 2405685:VMYU87NN 2405685:WWNJCJVG 2405685:ZFJGNIZJ 4656463:7UTAZK7R
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Bangladesh Back-to-School Campaign - Kaye, Tom; Chuang, Rachel; Moss Coflan, Caitlin; Haßler, Björn (EdTech Hub, 2020)
The EdTech Hub received a request from the FCDO Bangladesh team to provide a topic brief identifying best practices from previous back-to-school campaigns following disruptions. Key themes of effective school re-openings are examined in the context of modalities used to deliver distance learning (e.g., radio, television).
ZenodoArchiveID: 3865298 previousshortDOI: 10/ghgk6p previousshortDOI: 10/ghgk6p previousDOI: 10.5281/zenodo.3865298 shortDOI: 10/ghgk6p KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3865298 10.53832/edtechhub.0020 10/ghgk6p 2129771:2BEHBMUH 2129771:C6TREICJ 2129771:GQ4U9R5Z 2129771:QFFBWT4D 2339240:H8RZC7AY 2339240:T5DE93E2 2405685:3HP24UTI 2405685:CEADG684 2405685:H52W8E9M 2405685:HFKVA2IQ 2405685:U2AQUAZ2 2486141:B8P7D4EU
Keywords: C:Bangladesh; COV:COVID and reopening of schools; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _yl:g; _zenodo:submitted; _zenodoETH; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

National education sector investment plan - UNICEF (Government of Malawi, 2020)
Ministry of Education
KerkoCite.ItemAlsoKnownAs: 2339240:89TGACYY 2405685:MNE7VZEZ

An inclusive approach to searching for evidence on EdTech in low- and middle- income countries - Brugha, Meaghan (EdTech Hub, 2020)
A blog post by Meaghan Brugha and Katy Jordan. A searchable database The EdTech Hub has undertaken a large-scale search for publications on technology use in education in low- and middle- income countries. During this process, we created an internal research database. This is searchable through the use of a variety of filters, such as …
EdTechHub.Source: <this> EdTechHub.Source: 2405685:BGLPB3AG KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3911079 2129771:86J5A5RJ 2405685:6TX2RFBC 2405685:BGLPB3AG
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoODE

Unlocking data to tell the story of education in Africa: webinar summary & synthesis - Adam, Taskeen; Agyapong, Samuel; Asare, Samuel; Heady, Lucy; Wairimu, Wacharia; Mjomba, Renaldah; Mugo, John; Mukiria, Faith; Munday, Gemma (Zenodo, 2020)
[No description available.]
KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4279156 10.5281/zenodo.4279156 2129771:XYEJSVYW 2339240:59XYS4NB 2339240:EETQSD8S 2339240:HZTGKNN9 2405685:2W6A2G3H 2405685:6KDDB8UA 2405685:MS5GH9KJ 2405685:S9MFQ8KB
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Messaging Apps, SMS, and Social Media: A Rapid Evidence Review - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing research on the use of mobile phone-based messaging (including SMS, and messaging through apps such as WhatsApp) to support education in low- and middle-income countries (LMICs). This topic was chosen as the focus for a RER in response to the Covid-19 pandemic and school closures, as this form of technology has been adopted as part of some countries’ methods of providing continuing education during closures and disruption. As such, the overall purpose of this document is to summarise the existing research literature around messaging, so that the existing evidence can be used to inform ongoing responses to the pandemic. The findings are intended to be of use to educational decision makers, including donors and those in government and NGOs, to inform responses to the current pandemic.
ZenodoArchiveID: 4556938 PreviousDOI: 10.5281/zenodo.4058181 PreviousDOI: 10.5281/zenodo.4477015 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4058181 10.5281/ZENODO.4556938 10.5281/zenodo.4477015 10.5281/zenodo.4556938 2339240:8QFLYEYK 2339240:ATYZFQ8R 2339240:CUBEJEWS 2339240:LCAUL9ZC 2339240:NISQD6JT 2339240:T2Z992XW 2339240:XMQV9Y56 2339240:YGQCMSDP 2405685:2GE8ESCR 2405685:4G8DT7ZB 2405685:4JM6QWPH 2405685:5NMCR3LL 2405685:EQVI8NMV 2405685:IU849P3E 2405685:MMTHETFR 2405685:PY3CXCH9 2405685:QSD5LYSF 2405685:XHBPFYVC 2405685:Z7P9NRWJ
Keywords: Covid-19; LMICs; SMS; Social media; TPD; WhatsApp; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; educational technology; mobile learning; refugee education; teacher professional development; text message; ⛔ No DOI found

15 EdTech research papers that we share all the time - Moss, Caitlin (EdTech Hub, 2020)
We hope you saw our recent blog post responding to questions we often get about interesting large-scale EdTech initiatives. Another question we are often asked is: “What EdTech research should I know about?” As Sara’s blog post explains, one of the Hub’s core spheres of work is research, so we ourselves are very interested in […]
Library Catalog: edtechhub.org Section: general shortDOI: 10/ghgk6c KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3690149 10/ghgk6c 2339240:6LUYX6ZR 2339240:AS8A9UGV 2405685:CV2HG6CJ 2405685:FI72KCVG 2405685:JTA347FP 2405685:N2YMVN4S 2405685:TEVH3TNS
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Child-directed Tablet-based Learning: Project Launch, Monitoring, and Improvement Toolkit - Imagine Worldwide (2020)
KerkoCite.ItemAlsoKnownAs: 2405685:MJ592UKH

Child-directed Tablet-based Learning: Project Preparation Toolkit - Imagine Worldwide (2020)
KerkoCite.ItemAlsoKnownAs: 2405685:T7BK22I4

Education during the COVID-19 crisis: opportunities and constraints of using EdTech in low-income countries - David, Raluca; Pellini, Arnaldo; Jordan, Katy; Philips, Toby (Zenodo, 2020)
Key points: Technology can help mitigate the effects of the educational crisis and closures of schools, but ed-tech is not a silver bullet and governments need to have realistic expectations about what it can achieve The digital divide means that internet and mobile network access varies greatly in middle- and low-income countries Governments can provide immediate support by informing teachers about simple grassroots platforms where they can share their own ed-tech solutions Educational TV and radio broadcasts in combination with SMS are effective communication channels between educators and students when the internet connectivity is poor or not available It will be important for education authorities to begin planning how in 12-months’ time they will diagnose and treat the learning gaps that have emerged during the crisis.
shortDOI: 10/ghgnd7 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3750976 10/ghgnd7 2339240:3CKN9C4K 2339240:5AHKKQF6 2405685:92ZVGWNU 2405685:CT8JMZEU
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _zenodoETH; covid-19; crisis education; distance education; education; education policy; educational technology; emergency education; pandemic education; school closures; schools

The effect of Covid-19 on education in Africa and its implications for the use of technology - eLearning Africa; EdTech Hub (EdTech Hub, 2020)
ZenodoArchiveID: 4749652 previousDOI: 10.5281/zenodo.4018774 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4749652 2339240:B796SJQD 2339240:DI5RWJ4S 2405685:6MJNV8GC 2405685:TFLZLVTW
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Child-directed Tablet-based Learning: Toolkits for project design, preparation, and implementation - Imagine Worldwide (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:PNMXVDQ2 2405685:A4NNJNSJ 2405685:GBIY52AG

Effective Use of EdTech for Remedial Learning Programmes: Considerations for Mongolia - Upadhyay, Arjun; Shoobridge, James; Moss Coflan, Caitlin (EdTech Hub, 2020)
This document was produced in response to a request from the World Bank Mongolia team to: 1. Outline the evidence of effective practices on remedial education generally. 2. Explore appropriate uses of EdTech to support remedial education. 3. Summarise the implications of these findings for Mongolia.
previousDOI: 10.5281/zenodo.3958080 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3958080 10.5281/zenodo.5651111 2339240:3DJBGPQM 2339240:AWK2HEZ5 2405685:IJGQTHH9 2405685:UMZVQ4TV 2405685:ZEDSYPGH
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted

Impact de la pandémie de COVID-19 sur l’éducation en Afrique et incidence sur le recours aux technologies: Sondage sur l’expérience et les opinions des éducateurs et spécialistes de technologies - eLearning Africa; EdTech Hub (2020)
ZenodoArchiveID: 4749654 previousDOI: 10.5281/zenodo.4018774 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4749654 2405685:39XPD5EM 2405685:QZ2FJC4E
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⚠️ Invalid DOI

Educational Television: A Rapid Evidence Review - Watson, Joe; McIntyre, Nora (EdTech Hub, 2020)
This Rapid Evidence Review (RER) gives an overview of the recent literature concerning how the use of educational television might support children’s learning in low- and middle-income countries (LMICs). In this review, educational television is defined as television designed with research-based knowledge of how children use and understand television that systematically incorporates academic or social curricula into its content. In low-income contexts, educational television material could be delivered through videos played in schools that are supported by corresponding teacher guidance (e.g. the Mexican school-based T elesecundaria programme), or broadcast on public channels (e.g. the Tanzanian animation, Ubongo Kids). As such, certain educational television projects are capable of functioning even in circumstances where access to formal schooling facilities is restricted. This review therefore provides information that is particularly valuable in the context of the COVID-19 pandemic.
ZenodoArchiveID: 4556935 PreviousDOI: 10.5281/zenodo.4476991 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3956366 10.5281/zenodo.3956366 10.5281/zenodo.4476991 10.5281/zenodo.4556935 2259720:BFY7A76P 2339240:3WZUWHB3 2339240:CVI8639W 2339240:G8MSWBJC 2339240:IF3IMDSW 2339240:NUYRVP8T 2339240:UXMEFECL 2405685:BVXSZ7G4 2405685:BZFLWXG6 2405685:DPRU64AB 2405685:FMULV6ZI 2405685:TJ95P4G4 2405685:UJF6X47J 2405685:UVB294JN 2405685:Y3XDX8FW 4803016:WC4XVPPN
Keywords: L:English UXZJW5DR; P:Evidence review VCMFM9ZD; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:P:Girls ED5GMBNU; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _P:Evidence review VCMFM9ZD; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:P:Girls ED5GMBNU; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2405685:MWNVG7LR

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2405685:MWNVG7LR

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2405685:MWNVG7LR
Keywords: auto_merged